Constrained optimal discriminating designs for Fourier regression models - Stefanie Biedermann; Holger Dette; Philipp Hoffmann (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
In this article, the problem of constructing efficient discriminating designs in a Fourier regression model is considered. We propose designs which maximize the efficiency for the estimation of the coefficient corresponding to the highest frequency subject to the constraints that the coefficients of the lower frequencies are estimated with at least some given efficiency. A complete solution is presented using the theory of canonical moments, and for the special case of equal constraints the optimal designs can be found analytically.
Keywords: 519; Constrained optimal designs; trigonometric regression; D1-optimal designs; Chebyshev polynomials; canonical moments